A study on the consumption of coriander (Coriandrum sativum L.) and consumers' perception of its functional properties (Research, Society and Development, 2022)
Coriander (Coriandrum sativun L.) is a vegetable widely produced and consumed in Brazil being widely used as a condiment in many dishes. It has an excellent nutritional value as a source of calcium, iron, vitamin C. Furthermore it has functional properties such as anti-inflammatory, antioxidant and antimicrobial. Although it has so many benefits, there are few studies in this field that specifically analyze the use of that vegetable as condiment in food exploring its potential to add flavor. This way, this research carried out a survey on the consumption of coriander as condiment and evaluated the profile of consumers and their knowledge about that vegetable. It was found that coriander is consumed by 67.7% of interviewees mainly those who live in the Northeast and North regions where coriander is traditionally used in cooking. However, there is still a portion (32.3%) of consumers who still reject it. As a substitute for other condiments, coriander is more often used instead of parsley and the main food to which it is added is fish. When one takes into account the purchase intention of industrialized products with the addition of coriander, it is observed that seasoned cheese and snacks are the most cited. In addition, it was possible to observe that flavor is the main motivator for consumption ahead of health-related attributes. Thus, it was possible to observe that consumers are still unaware of the main beneficial characteristics of coriander. In this way, there is the possibility of developing new products using coriander as well as the relevance of carrying out studies with an emphasis on this flavouring.